Rapid onset of severe septic shock in the pregnant mouse†. Issue 2 (3rd September 2018) - Zöllner, Julia; Lambden, Simon; Nasri, Noor Mohd; Leiper, James; Johnson, Mark R
Abstract: Aims: Globally, sepsis is a major cause of mortality through the combination of cardiovascular collapse and multiorgan dysfunction. Pregnancy appears to increase the risk of death in sepsis, but the exact reason for the greater severity is unclear. In this study, we used polymicrobial sepsis induced by cecal ligation and puncture (CLP) and high-dose intraperitoneal lipopolysaccharide (LPS; 10 or 40 mg, serotype 0111: B4) to test the hypotheses that pregnant mice are more susceptible to sepsis and that this susceptibility was mediated through an excessive innate response causing a more severe cardiovascular collapse rather than a reduction in microbe killing. Methods and Results: Initial studies found that mortality rates were greater, and that death occurred sooner in pregnant mice exposed to CLP and LPS. In pregnant and nonpregnant CD1 mice monitored with radiotelemetry probes, cardiovascular collapse occurred sooner in pregnant mice, but once initiated, occurred over a similar timescale. In a separate study, tissue, serum, and peritoneal fluid (for protein, flow cytometry, nitric oxide, and bacterial load studies) were collected. At baseline, there was no apparent Th1/Th2 bias in pregnant mice. Post CLP, the circulating cytokine response was the same, but leukocyte infiltration in the lung was greater in pregnant mice, but only TNFα levels were greater in lung tissue. The bacterial load in blood and peritoneal fluid was similar in both groups. Conclusion: Sepsis-related mortality was markedly greater in pregnant mice. Cardiovascular collapse and organ dysfunction occurred sooner in pregnancy, but bacterial killing was similar. Circulating and tissue cytokine levels were similar, but immune cell extravasation into other organs was greater in pregnant mice. These data suggest that an excessive innate immune system response as shown by the exaggerated lung infiltration of leukocytes may be responsible for the greater mortality. Approaches that reduce off-site trafficking may improve the prognosis of sepsis in pregnancy. Abstract : Overall, our data suggests that severe septic shock in pregnancy occurred earlier and resulted in greater mortality. Markedly greater inflammatory cell extravasation in the lungs suggests that this off-target effect may mediate the high rates of mortality.